2022
DOI: 10.1253/circrep.cr-22-0068
|View full text |Cite
|
Sign up to set email alerts
|

Intravascular Lithotripsy for Vessel Preparation in Calcified Coronary Arteries Prior to Stent Placement ― Japanese Disrupt CAD IV Study 1-Year Results ―

Abstract: Background: Intravascular lithotripsy (IVL) delivers acoustic pressure waves to modify calcium, enhance vessel compliance, and optimize stent deployment. The Disrupt CAD IV study enrolled patients with severe coronary artery calcification and demonstrated low 30-day major adverse cardiovascular events (MACE) and high procedural success following IVL with no final serious angiographic complications. To date, long-term outcomes have not been reported. This analysis evaluates 1-year outcomes of Disrupt CAD IV. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…The J2T Registry was a multicenter registry of rotational atherectomy for calcified coronary lesions that enrolled 1,090 Japanese patients with similar characteristics to those in CAD IV. The 1-year outcomes for MACE (23%), all-cause death (8%), TVR (14%), and TLR (17%) following rotational atherectomy were markedly greater than those observed in CAD IV, 13 with the incidence of MACE continuing to rise to 46.7% during a median follow-up period of 3.8 years. 20 Similar findings were reported in the Coronary Orbital Atherectomy System Study (COAST), which reported 1-year rates of MACE, TVR, and TLR of 22.2%, 9.4%, and 6.3%, respectively.…”
Section: Patientsmentioning
confidence: 80%
See 2 more Smart Citations
“…The J2T Registry was a multicenter registry of rotational atherectomy for calcified coronary lesions that enrolled 1,090 Japanese patients with similar characteristics to those in CAD IV. The 1-year outcomes for MACE (23%), all-cause death (8%), TVR (14%), and TLR (17%) following rotational atherectomy were markedly greater than those observed in CAD IV, 13 with the incidence of MACE continuing to rise to 46.7% during a median follow-up period of 3.8 years. 20 Similar findings were reported in the Coronary Orbital Atherectomy System Study (COAST), which reported 1-year rates of MACE, TVR, and TLR of 22.2%, 9.4%, and 6.3%, respectively.…”
Section: Patientsmentioning
confidence: 80%
“…10 Secondary endpoints at 1 year, including target lesion failure (TLF; 6.3%), MACE (9.4%), and stent thrombosis (ST; 0.0%), have also been published. 13 The current analysis presents the final outcomes of the Disrupt CAD IV study and evaluated secondary endpoints at 2 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Four prospective, single‐arm, multicenter studies have been conducted to assess the safety and effectiveness of IVL in patients with de novo heavily calcified coronary lesions with encouraging results (Table 1): Disrupt coronary artery disease (CAD) I, 11 Disrupt CAD II, 12 Disrupt CAD III, 13 and Disrupt CAD IV 14 . The Disrupt CAD IV study demonstrated good long‐term (1 year) outcomes (MACE rate = 9.4%).…”
Section: Introductionmentioning
confidence: 99%
“…Clinical outcomes with IVL have been favorable up to 1 year after PCI. 8 However, it remains unclear whether IVL is time points using anatomic landmarks such as characteristic calcified plaque morphology and side branches.…”
mentioning
confidence: 99%